2019
DOI: 10.1111/1440-1703.1267
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between soil properties and leaf functional traits in early secondary succession of tropical montane cloud forest

Abstract: Recognizing soil properties associated with the plant strategy in relation to use and acquisition of resources during early secondary succession (ESS) is an important issue in plant ecology. We analyzed the relationship between 10 leaf functional traits (LFTs) and 17 soil properties including soil nutrients, transformation flows and pH along a plant chronosequence spanning first 40 years of ESS in a tropical mountain cloud forest. To recognize the multivariate variation of soil properties, a principal componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 79 publications
(135 reference statements)
2
10
0
1
Order By: Relevance
“…In the assessment of the integrated soil fertility quality index (SFQI PCA ), principal component analysis (PCA) has been widely used [49]. According to PCA, such variations in the relative significance of a strategy could be mediated by changes in soil conditions [50]. Soil nutrients, such as soil TP, contributed positively to the primary axis of PCA [50].…”
Section: Soil Properties Differences In Two Different Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the assessment of the integrated soil fertility quality index (SFQI PCA ), principal component analysis (PCA) has been widely used [49]. According to PCA, such variations in the relative significance of a strategy could be mediated by changes in soil conditions [50]. Soil nutrients, such as soil TP, contributed positively to the primary axis of PCA [50].…”
Section: Soil Properties Differences In Two Different Yearsmentioning
confidence: 99%
“…According to PCA, such variations in the relative significance of a strategy could be mediated by changes in soil conditions [50]. Soil nutrients, such as soil TP, contributed positively to the primary axis of PCA [50]. On the other hand, Chen et al [49] reported that first PC (PC1) was highly correlated with TN.…”
Section: Soil Properties Differences In Two Different Yearsmentioning
confidence: 99%
“…A soil's capacity for water infiltration/retention and nutrient retention will depend on its physical properties: Clayey soils can retain more water and nutrients than sandy soils because they are formed by small particles, with relatively small spaces that increase water adsorption (Brady and Weil 2013;Perkins et al 2013;Neves et al 2016). Certain leaf traits of plants often covary with specific soil properties, and numerous examples of such adjustments have been reported for tropical trees (Moraes et al 2017;Hernández-Vargas et al 2019;Vitória et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Plant traits such as shoot traits (shoot N and C, leaf dry matter content) and root traits (root N, root C/N ratio, root dry matter content) can be used to predict soil properties and ecosystem functions in temperate grasslands (Long et al, 2019). Soil properties and plant functional traits are important for regulating the functioning of tropical cloud forests (Hernández-Vargas et al, 2019), while soil heterogeneity and plant functional traits can predict variation in species distribution in subtropical forests (Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%